The Influence of Motivation, Incentives on ASN Professionalism is Mediated by Job Satisfaction in the Badung Regency Governmen - Frisky F. Liando; A. A. N. Oka Suryadinatha Gorda (Quantitative Economics and Management Studies, 2024)
The purpose of this research is to find out and analyze the influence of motivation and incentives on the job satisfaction of Badung Regency Government ASN, then to find out and analyze the influence of motivation, incentives and job satisfaction on the professionalism of Badung Regency Government ASN, then to find out and analyze the influence of the role of job satisfaction in mediating the influence of motivation and incentives on the professionalism of Badung Regency Government ASN. The population of this research is the State Civil Apparatus (ASN) in the Badung Regency Government, totaling 6,890 employees. The number of respondents in the sample was between 90 and 180 respondents. Data collection in this research used a questionnaire. The data analysis technique consists of descriptive analysis and inferential analysis using the Partial Least Square (PLS) approach. The results show that: Motivation has a positive and significant effect on job satisfaction. Incentives have a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on professionalism. Incentives do not have a significant effect on professionalism. Job satisfaction has a positive and significant effect on professionalism. The influence of motivation on professionalism through job satisfaction is positive and significant. The effect of incentives on professionalism through job satisfaction is positive and significant.